2016
DOI: 10.1007/s11207-016-0853-x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Revised Sunspot Record on Solar Irradiance Reconstructions

Abstract: Reliable historical records of total solar irradiance (TSI) are needed for climate change attribution and research to assess the extent to which long-term variations in the Sun's radiant energy incident on the Earth may exacerbate (or mitigate) the more dominant warming in recent centuries due to increasing concentrations of greenhouse gases. We investigate potential impacts of the new Sunspot Index and Long-term Solar Observations (SILSO) sunspot-number time series on model reconstructions of TSI. In contempo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 51 publications
0
61
2
Order By: Relevance
“…Indeed, SSI models have not yet been thoroughly trained and tested with this new sunspot number. Recent results by Kopp et al (2016) suggest that this revision has little impact after 1885, and leads to greater solar-cycle fluctuations prior to that. Note that the NRLSSI version employed here uses the GSSN (Hoyt and Schatten, 1998), while SATIRE uses the annually averaged international sunspot number (v1.0).…”
Section: Proxies Usedmentioning
confidence: 99%
“…Indeed, SSI models have not yet been thoroughly trained and tested with this new sunspot number. Recent results by Kopp et al (2016) suggest that this revision has little impact after 1885, and leads to greater solar-cycle fluctuations prior to that. Note that the NRLSSI version employed here uses the GSSN (Hoyt and Schatten, 1998), while SATIRE uses the annually averaged international sunspot number (v1.0).…”
Section: Proxies Usedmentioning
confidence: 99%
“…In the SILSO sunspot numbers (Clette et al, 2015), also shown in Figure 2a, eighteenth century solar cycles have notably larger amplitudes than in the Hoyt and Schatten (1998) group sunspot number; the SILSO sunspot number at the peak of solar cycle 19 is only 1.2 times larger than the peak of cycle 4. Kopp et al (2016) describe and compare the dependence of the NRLTSI2 and SATIRE reconstructions of TSI since 1610 on the adopted sunspot number record. Kopp et al (2016) describe and compare the dependence of the NRLTSI2 and SATIRE reconstructions of TSI since 1610 on the adopted sunspot number record.…”
Section: Sunspotsmentioning
confidence: 99%
“…For estimating solar irradiance between 1882 and the space era, the NRLTSI2 and NRLSSI2 models use direct observations of the areas and locations of sunspots made by the Royal Greenwich Observatory from 1882 to 1976 (Willis et al, 2013) to calculate a sunspot darkening function, which is scaled by 68% for cross calibration with that from the SOON observations (Coddington et al, 2016;Kopp et al, 2016). The facular index is a combination of Ca II K plage areas and the 10.7-cm solar radio flux after 1950 and sunspot numbers before then (Lean et al, 2001).…”
Section: The 1610-2016 Cementioning
confidence: 99%
See 1 more Smart Citation
“…The most critical implication of these series is that they yield different long-term trends for the activity of the Sun ; Kopp et al 2016). Over the 19th and 20th centuries, ClLi16 and SvSc16 show no trend, while HoSc98 and UEA16 show an increase in solar activity.…”
Section: Introductionmentioning
confidence: 99%